A Robust Molecular Catalyst Generated In?Situ for Photo- and Electrochemical Water Oxidation; ChemSusChem; Vol. 10, iss. 5 - Hassan H. A. Yo. Hussein Abdelazeem Younus; Ahmad N. Nazir; Chughtai A. H. Adeel; Vandichel M. Matthias; Busch M. Michael; Van H. K. Hecke Kristof; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Song Sh. Shaoxian; Verpoort F. V. K. Frensis Valter Kornelius (2017, 2017)
Title screen